Space structures 4 - Parke, G. A. R.; Howard, C. M., Mr. (Thomas Telford, 1993)
Includes the diversity of constructions on space structures ranging from anten reflectors and masts positioned in space, to equally exciting terrestrial structures. This collection is suitable for engineers, architects and other professionals engaged in the planning, design, fabrication. and erection of novel constructions.